A influência da hallyu wave na política internacional da Coreia do Sul para a Tailândia (2010-2020) - Paula, Esther Sharapin de (2023)
The present work has as its general objective to understand how the Korean culture, the Hallyu Wave, influences the international policy of South Korea towards Thailand, intending to verify if and in what way the Korean culture has contributed, through its accessories as the K-POP, K-Dramas, icons and tourist attractions, for the transformation and consolidation of political and economic relations between Thailand and South Korea in the last ten years, to understand how the Hallyu Wave tries to recover Korea's identity of the South and analyze South Korea-Thailand relations from the influence of the Hallyu Wave. The theme is limited to understanding how South Korea's international policy is affected by its culture in relation to Thailand between 2010 and 2020. It is based on soft power theory and the concept of cultural diplomacy. It was found that South Korea's international policy towards Thailand is influenced by South Korean culture, since, with the increase in consumption of Korean products in Thailand, contact with the country has grown and brought the country closer politically, economically and culturally.